Linguistic emotivity : centrality of place, the topic-comment dynamic, and an ideology of pathos in Japanese discourse - Maynard, Senko K. (Pragmatics & beyond, 2002)
Linguistic Emotivity explores expressive and emotive meanings in Japanese from the perspective of the Place of Negotiation theory. The Place of Negotiation theory provides a framework for understanding how linguistic signs function in the place of communication (in cognitive, emotive, and interactional places). The theory finds the indexicality of a sign fundamental and views meanings as being negotiated among interactants who share not only information but, more significantly, feelings. Using analytical tools recognized in conversation and discourse analyses, the book analyzes emotive topics).